Factors Impeding Implementation of Education Policies in the Pre-schools in Mokhotlong (International Journal of Scientific Research and Management (IJSRM), 2025)
The purpose of this investigation was to determine whether variables such as shortage of qualified teachers and lack of parental involvement in the education of their children impede implementation of education policies as well as establishing the challenges which hamper implementation of education policies. In this study, we adapted a mixed methods research design comprising quantitative and qualitative research representations. The population for the study was 51 people. The sample for quantitative part of the study was 34 respondents while that of the qualitative study was also 34 participants. The results of this investigation revealed that shortage of qualified teachers impedes implementation of education policies. The study also revealed that lack of parental involvement in the education of their children does not affect implementation of education policies. Finally, the findings of this study showed that factors such as imposition of policies on a target population, lack of supervision as well as poor infrastructure hamper implementation of education policies. On the basis of the results of this study, it was concluded that shortage of qualified teachers is a variable which impedes implementation of education policies and also that imposition of policies on people as well as poor infrastructure hamper implementation of education policies